(untitled) (Journal of Management & Business, 2025)
Corporate social responsibility (CSR) by small and medium enterprises (SMEs) is susceptible to various organizational factors. This study investigated how gender, business structure, employee size, and turnover impact SMEs’ CSR in a developing economy in response to HIV/AIDS. The aim is to explore how organizational factors function as determining agents and impact CSR in SMEs. We conducted a quantitative survey with a 7-point Likert-type questionnaire, gathering data from 170 SME owners and owner-managers. Statistical analysis included descriptive statistics, One-way ANOVA, and independent sample t-tests. The results indicate that gender did not significantly impact CSR entrepreneurs’ CSR attitudes and behaviours. Business structure played a crucial role in shaping CSR activities, notably concerning HIV/AIDS initiatives for employees, the community, and customers. Employee size significantly affected employee and customer-oriented HIV/ AIDS CSR activities but not community-oriented ones. Turnover significantly influenced employee and customer-oriented CSR activities but did not significantly impact community-oriented CSR activities. These findings add to emerging discourse about how organizational factors affect small business social responsibility practices.